2019
DOI: 10.1038/s41746-019-0077-1
|View full text |Cite
|
Sign up to set email alerts
|

Preference for in-person psychotherapy versus digital psychotherapy options for depression: survey of adults in the U.S

Abstract: Several barriers complicate access to psychotherapy for depression, including time commitment, location of services, and stigma. Digital treatment has the potential to address these barriers, yet long term use of digital psychotherapy is poor. This paper presents data from a mixed-methods, online survey to document concerns patients with depression face when given the choice of in-person psychotherapy and digital psychotherapy. Participants were 164 adults living in the United States who had previously used or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(55 citation statements)
references
References 37 publications
3
51
0
1
Order By: Relevance
“…It would also be important for future research to pinpoint the reasons why few people prefer e‐therapy programs over face‐to‐face psychotherapy. For example, some have speculated low e‐therapy preference rates to be a result of peoples' limited knowledge of the evidence supporting e‐therapy, suspicion of psychological interventions without direct human contact, and concerns with privacy and sensitive personal information in an online environment (Batterham & Calear, 2017; Renn, Hoeft, Lee, Bauer, & Areán, 2019). Knowing the reasons for these low preference rates in the context of EDs could be important for addressing any misconceptions and concerns related to e‐therapy, thus potentially increasing rates of online therapy acceptance, help‐seeking, and engagement.…”
Section: Discussionmentioning
confidence: 99%
“…It would also be important for future research to pinpoint the reasons why few people prefer e‐therapy programs over face‐to‐face psychotherapy. For example, some have speculated low e‐therapy preference rates to be a result of peoples' limited knowledge of the evidence supporting e‐therapy, suspicion of psychological interventions without direct human contact, and concerns with privacy and sensitive personal information in an online environment (Batterham & Calear, 2017; Renn, Hoeft, Lee, Bauer, & Areán, 2019). Knowing the reasons for these low preference rates in the context of EDs could be important for addressing any misconceptions and concerns related to e‐therapy, thus potentially increasing rates of online therapy acceptance, help‐seeking, and engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Some clients using telephone or text-based therapies have reported feeling able to talk more freely and feeling less concerned about how others may judge them ( Turner, 2015 ). A recent adult survey suggested that 72% of adults would like to try digital psychotherapy, but when forced to choose between modalities, the majority preferred face-to-face ( Renn et al, 2019 ).…”
Section: Client Perspectivesmentioning
confidence: 99%
“…Self-guided digital technologies, including self-help apps and chatbots, have been proposed as solutions because of the advantages they provide in access and cost, but they are not a panacea, displaying several limitations [ 9 , 10 ]. Their reach is limited because people seeking mental health support typically prefer face-to-face over computerized therapy [ 11 , 12 ]. Their efficacy is limited because digital tools often fail to motivate and engage users [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%